Enhanced sensitivity to punctate painful stimuli in female patients with chronic low back pain - Puta, Christian; Magerl, Walter (BMC neurology, 2012)
Background: Chronic low back pain (CLBP) has been shown to be associated with various pathophysiological changes at several level of the sensorimotor system, pointing to a general hypersensitivity in CLBP patients. The aim of the present study was to investigate signs of generalized mechanical pain hypersensitivity in CLBP patients on the hand and on the painful site of the back. Methods: Pinprick stimulation according to a validated standardized quantitative sensory testing protocol was used in 14 female CLBP patients and 14 healthy controls (HC) matched for sex and age. Stimulus response functions to pinprick stimulation on the skin were examined at the affected back and reference sites (hand palmar and hand dorsum). Data from CLBP patients were compared with HC and with reference data from the German Research Network on Neuropathic Pain. Results: We found significant differences in the stimulus response functions between CLBP patients and HC. Pain ratings to the pinpricks were increased for low and moderate pinprick stimuli in CLBP patients. Importantly, this kind of specific pinprick hyperalgesia was found not only for the affected body site (back), but also for the remote reference sites (hand dorsum and hand palmar). Conclusions: We interpret our results as pointing to changes in the nociceptive processing in CLBP at higher levels of the neuraxis, possibly thalamus and/or attentional control, rather than changes of spinal processing. Alternatively, there might be a higher vulnerability to noxious stimulation in CLBP patients.